ANALISA KOMPOSISI DAN KEANEKARAGAMAN JENIS TEGAKAN PENYUSUN HUTAN TEMBAWANG JELOMUK DI DESA META BERSATU KECAMATAN SAYAN KABUPATEN MELAWI - Nuraina, Ismi; Fahrizal, .; Prayogo, Hari (JURNAL HUTAN LESTARI, 2018)
Tembawang is a indigenous forest that is the local wisdom of Dayak tribe in West Kalimantan. This study aims to record the composition, species diversity and dominance of tree species present in the forest Tembawang Jelomuk. Analysis of vegetation on forest Tembawang Jelomuk using purposive sampling method. The results of observational data analysis showed that the dominant vegetation species with the highest important value index for the growth rate of the seedling phase were karet (Hevea brasiliensis) of 47.02% and petai (Parkia speciosa) of 22.54%, the sapling stage was karet (Hevea Brasiliensis) of 52.23% and kapuak (Parakeocarpus Bracteatus) of 25.10%, the pole phase is the leban (Vitex pubescens) of 87.18% and karet (Hevea brasiliensis) of 53.74% and the tree phase is durian (Durio Zibethinus) of 57.54% and leban (Vitex pubescens) of 37.91%. The result of analysis for dominance index value (C) at Tembawang Jelomuk pole level is vegetation which has the highest dominant index value among the three other growth levels. Species Tembawang Jelomuk variety of all growth rates are in the range with values found more than 1 and less than 3 (1 â‰¤ H â‰¥ 3), which means that the index of diversity of species owned by Tembawang Jelomuk include medium. The results of the index analysis of abundance types of seedling level of 0.84, the level of sapling of 0.88, the pole level of 0.80 and the level of trees of 0.84, Overall index of species abundance found in Tembawang Jelomuk is evenly at all growth rates.Keywords: Composition, Diversity Type, Tembawang Jelomuk